Comparison of computed tomography and guided bronchoscopy in the diagnosis of pulmonary nodules: A systematic review and meta-analysis - Wang Yilin; Liang Xianhe; Zhang Haitao; Hao Jinhua; Wei Min (Open Medicine, 2025)
To compare the diagnostic effects of computed tomography (CT) and bronchoscopy guided biopsy on pulmonary nodules.